A Unique Case of Primary Cutaneous Adenoid Cystic Carcinoma Associated with Aplasia Cutis Congenita in a Four-Year-Old Female: A Case Report - Andrea Zulli; Alessandra Martin; Flavio Facchini; Riccardo Coletta; Angela Tamburini; Teresa Oranges; Cesare Filippeschi; Andrea Bassi; Anna Maria Buccoliero; Antonino Morabito (Children, 2022)
Introduction: Primary cutaneous adenoid-cystic carcinoma (PCACC) is a rare malignant tumour reported in only about 450 cases in the literature, with only two adolescent cases reported. PCACC seems to occur between the fifth and seventh decade of life, and the most frequent regions involved are head and neck (46%). Aplasia cutis congenita (ACC) has an incidence of 1:10,000, and it seems to be rarely associated with neoplastic lesions. Interestingly, the association between PCACC and ACC has, so far, never been described. Methods: We report a case of PCACC in the scalp associated with ACC in a four-year-old patient. Discussion: The patient was under follow-up at the dermatology unit, but suddenly a red lesion appeared within the ACC. This red, ulcerated area increased rapidly over six months, so it was surgically removed, and the pathological examination results were suggestive for cribriform PCACC. According to the guidelines for skin tumours, the patient underwent widening resection, and an advancement-sliding skin flap was performed to recreate the scalp. After one year of follow-up, the patient has no local or widespread recurrence of the PCACC, and the surgical scar appears to have healed well. Conclusions: This clinical case is the first known patient with PCACC associated with ACC. A skin excision biopsy should be performed with wide margins to avoid a second widening resection of skin in a similar scenario. Genetic studies may help to identify the origin of this rare association.